The body and beauty - Bieńko, Mariola (Body and society. Sociology of the body in research and theoretical concepts, 2023)
This chapter is an attempt to reflect on the invasive beautifying body practices in contemporary consumer culture. The issues raised in this chapter relate to several problem areas. The first one concerns physical attractiveness as an individual and socio-cultural project in the private and public space. The control over one’s body image is linked to a symbolic representation of one’s identity, which is more and more often becoming a matter of choice. Body management is related to a tendency to auto-create and “„create oneself” as well as to the re-evaluation of beauty as a social value. The second problem area is focused on the procedures of aesthetic surgery, which are interpreted in the mass culture as a necessity due to the compulsion to have a beautiful body and the phenomenon of old-age “„disgrace”. The plastic surgery culture (“„nip and tuck”) is a consequence of the consumer logic of late capitalism and the neoliberal conception of social life. The theoretical approaches presented in this chapter as well as the results of studies indicate to what degree carrying out the project of an “„improved”, “„beautiful” human having specified physical parameters is an expression of control and oppression, and to what degree it is an expression of one’s individualism and emancipation. The text explains the differences between cosmetology, aesthetic medicine, aesthetic, plastic and reconstructive surgery; the descriptions of the categories of body dysmorphic disorder, aesthetic work, cosmetic gaze as well as the phenomena of body shaming, body policy, body neutrality/body positivity, etc. are also offered.